The Human Security in Buddhist Perspective - สิริเดชนนท์, พลสรรค์; ปันธิยะ, พูนชัย (Ganesha Journal, 2018)
This article describes the three aspects of human security: 1. The Physical Security implies to the Physical Happiness with the fulfillment of physical needs. There are five principles of the life longevity; 1) should not create any suffering to oneself; 2) be happy in the pursuit for happiness; 3) should eat food which is easy to digest or be hygienic; 4) have good behavior; and 5) should have good environment or good friend. On the other hands, there are the other three methods of physical security: (1) right speech (2) right action and (3) right livelihood. On the practical principles to achieve the life’s benefit and success are of the 4 basis for success and the contentment: 2. The Mental security implies to the cessation of suffering based on the development of meditation and wisdom in 3 aspects: the mental quality, the mental ability, and the mental health: and 3. The Social security implies to the Middle way practice with the true realization the causality that manifests all phenomena having entirely changed society.